2015
DOI: 10.1021/acs.chemmater.5b02340
|View full text |Cite
|
Sign up to set email alerts
|

Introducing Solubility Control for Improved Organic P-Type Dopants

Abstract: To overcome the poor solubility of the widely 8 used p-type dopant 2, 3,5,6-tetrafluoro-7,7,8,8-tetracyanoqui-9 nodimethane (F4TCNQ) 31,32 and 3,6-difluoro-2,5,7,7,8,8-75 In this paper, we first demonstrate a straightforward synthetic 88 route to soluble versions of F4TCNQ-type dopants by 89 substituting the cyano groups with either methyl or n-octyl f1 90 esters (Figure 1). A comprehensive study of the electro-91 chemical properties of these F4TCNQ analogues is performed 92 using cyclic voltammetry. Wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
122
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 97 publications
(130 citation statements)
references
References 64 publications
8
122
0
Order By: Relevance
“…A considerable number of studies have already shown that the molecular dopant F4TCNQ is able to p-type dope P3HT [24,26,30,31]. In this section, this molecular doping process is re-examined from the dopant diffusion perspective.…”
Section: Molecular Doping Of the Non-polar Layermentioning
confidence: 97%
See 4 more Smart Citations
“…A considerable number of studies have already shown that the molecular dopant F4TCNQ is able to p-type dope P3HT [24,26,30,31]. In this section, this molecular doping process is re-examined from the dopant diffusion perspective.…”
Section: Molecular Doping Of the Non-polar Layermentioning
confidence: 97%
“…It is clear that P3HT and F4TCNQ do not form a stable bilayer structure, but rather the P3HT is substantially doped by the F4TCNQ molecules, as seen by the reduced P3HT absorbance around 2.48 eV and the appearance of the broad peaks centered around 1.5 eV and 0.6 eV which are characteristics of P3HT þ polarons [24,25]. Based on the ground-state/polaron peak ratio, we can determine a doping concentration of~11 wt% [31], which agrees nicely with the amount of F4TCNQ we deposited. This result suggests that P3HT provides a good host for F4TCNQ and that when it is present, the F4TCNQ efficiently dopes the entire P3HT layer at room temperature with an unambiguous change in the optical absorbance.…”
Section: Molecular Doping Of the Non-polar Layermentioning
confidence: 99%
See 3 more Smart Citations